Minimization of Turnover Intention of Restaurant Employees Through Organizational Commitment - Shrestha, Indira (Journal of Nepalese Business Studies, 2025)
Employee turnover in the hospitality industry is becoming more challenging in today’s business arena. It is important to uncover the factors that might affect turnover. So this study attempted to analyze the impact of organizational commitment on restaurant employees' intention to leave the organization. (Affective commitment, continuance commitment, and normative commitment) as three factors of organizational commitment have been proposed as independent variables to see their impact on turnover intention, the dependent variable. One hundred sixty-three samples were surveyed from all the restaurant employees (population) located in the Lalitpur district of Kathmandu valley. Multiple regression analysis was applied to examine the effect of predictor variables on the dependent variable. The structured questionnaire was used to get the information from the respondents. Three factors of organizational commitment have an inverse significant effect on turnover intention. The results showed that affective commitment, continuance commitment, and normative commitment have a negative impact on turnover intention. Normative commitment is a more powerful factor in playing the role in leaving the organization. These findings support the existing literature related to the relationship between organizational commitment and turnover intention. Moreover, the result will help employers to focus more on normative commitment along with affective commitment, followed by continuance commitment to retain employees. Since the study has covered the restaurant employees of Lalitpur districts of Kathmandu Valley, future researchers are also suggested to cover Bhaktapur and Kathmandu districts as well.